Retail Warehousing in the City of Mississauga - Swan, Susan M. (My University, 1990)
The main focus of this paper is to investigate retail found in designated industrial districts within the City of Mississauga. Specifically, it will concentrate on the high order goods retailing or retail warehousing, its location and the planning policies that seek, in theory, to control its development. This is a new trend in retailing that should be investigated in more detail.
Keywords: retail, warehousing, Mississauga, industrial, high order goods